A Low-Field Temperature Dependent EPR Signal in Terraced MgO:Mn2+ Nanoparticles: An Enhanced Zeeman Splitting in the Wide-Bandgap Oxide - Peter V. Pikhitsa; Sukbyung Chae; Seungha Shin; Mansoo Choi (Journal of Spectroscopy)
Mn2+ ion doping is used as an electron paramagnetic resonance (EPR) probe to investigate the influence of low-coordination structural defects such as step edges at the surface of terraced (001) MgO nanoparticles on the electronic properties. Beside the well-known hyperfine sextet of Mn2+ ions in the cubic crystal field of MgO, an additional EPR feature with a striking nonmonotonous temperature dependent shift of the g-factor is observed in terraced nanoparticles in the temperature range from 4 K to room temperature. By linking the difference in the temperature dependence of the Mn2+ sextet intensity in cubic and terraced nanoparticles with the possible s-d exchange shift and enhanced Zeeman splitting we conclude that the novel EPR feature originates from the loosely trapped charge-compensating carriers at the abundant structural defects at the surface of terraced nanoparticles due to their exchange interaction with neighboring Mn2+ ions.